Hints of Planet Formation Signatures in a Large-Cavity Disk Studied in the Age-Pro Alma Large Program - Miley, J; Gonzalez-Ruilova, C (Institute of Physics, 2024)
Detecting planet signatures in protoplanetary disks is fundamental to understanding how and where planets form. In this work, we report dust and gas observational hints of planet formation in the disk around 2MASS J16120668-301027, as part of the Atacama Large Millimeter/submillimeter Array (ALMA) Large Program “AGE-PRO: ALMA survey of Gas Evolution in Protoplanetary disks.” The disk was imaged with the ALMA at Band 6 (1.3 mm) in dust continuum emission and four molecular lines: 12CO(J = 2-1), 13CO(J = 2-1), C18O(J = 2-1), and H2CO(J = 3(3,0)-2(2,0)). Resolved observations of the dust continuum emission (angular resolution of ∼150 mas, 20 au) show a ring-like structure with a peak at 0.″57 (75 au), a deep gap with a minimum at 0.″24 (31 au), an inner disk, a bridge connecting the inner disk and the outer ring, along with a spiral arm structure, and a tentative detection (to 3σ) of a compact emission at the center of the disk gap, with an estimated dust mass of ∼2.7−12.9 Lunar masses. We also detected a kinematic kink (not coincident with any dust substructure) through several 12CO channel maps (angular resolution ∼200 mas, 30 au), located at a radius of ∼0.″875 (115.6 au). After modeling the 12CO velocity rotation around the protostar, we identified a purple tentative rotating-like structure at the kink location with a geometry similar to that of the disk. We discuss potential explanations for the dust and gas substructures observed in the disk and their potential connection to signatures of planet formation. © 2024. The Author(s). Published by the American Astronomical Society.